If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2y + -1y + 3w = 0 Reorder the terms: 3w + 5y + 2y + -1y = 0 Combine like terms: 5y + 2y = 7y 3w + 7y + -1y = 0 Combine like terms: 7y + -1y = 6y 3w + 6y = 0 Solving 3w + 6y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6y' to each side of the equation. 3w + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 3w + 0 = 0 + -6y 3w = 0 + -6y Remove the zero: 3w = -6y Divide each side by '3'. w = -2y Simplifying w = -2y
| 4x+14=74-6x | | t^2-12t-45= | | 5(8k+8)= | | 5(x-2)=-45 | | 5(6-(3x-8))+5x=0 | | 2y(x+2)= | | 1=3x-4xy | | 10(n^2+n)-6(n^2-2)= | | 3x-(4x+4)=7x-12 | | 20x^2+2=20x^2-5x | | y-12=6-8y | | 1800-4t^2=0 | | 3x^4+x^3-8x^2-x+3=0 | | 7(n-6)+2=-36+8n | | 8i+3i=12i+9 | | 6w+10=4w-4 | | 10+6w=4-4w | | 5r+7=2r+19 | | 12-1y=6-8y | | 12-Y=6-8Y | | 1k-3k=6k+5-8k | | 1x+7x+20=4-3x | | 2.4x+2=0.2 | | 3.5x+3=0.2 | | 14x-4+12x=1+x | | 3d+2(d+1)=5(3d-7) | | 2x+7=5y+3 | | 2m+3(2m-7)=4+5(m+2) | | 11u-3=u-13 | | 5(v+2)=7(v+1) | | 5x-2=5+3x | | -3(z+3)=2(4-z) |